An Improvement Of Scrambling Technique By Using Modified Selected Mapping In Ofdm System - Khor, Eng Wong (Universiti Sains Malaysia, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) is a form of digital signal modulation format that is being used in many digital communication system, such as digital television, internet access, wireless network and 4G mobile communication. It is a method of encoding digital data on multiple carrier frequencies. Due to the high transmission speed and efficiency, OFDM is often been chosen to implement in many applications for communication purpose. However, the major drawback of OFDM system is the high Peak-to-Average Power Ratio (PAPR) which also resulting in the increase of Bit Error Rate (BER) and power consumption. Hence, PAPR become the most important issue to tackle. There are various techniques can be used to reduce PAPR. They generally can be classified into two groups, signal scrambling technique and signal distortion technique. This project proposed a method called Modified Selected Mapping (MSLM) scheme to reduce the PAPR. Basically, this technique is the combination of selected mapping (SLM) and linear block coding method which both of them are considered as signal scrambling technique. The project’s objectives are to develop a system to reduce the PAPR in OFDM system by using MSLM scheme and to determine how the number of subcarriers affect the PAPR performance of OFDM system. In conclusion, MSLM scheme was able to reduce the amount of PAPR 8.27% more than the conventional SLM in average. This research also found out that the PAPR of the system increases with the number of subcarriers used.